Impact of oral disease and disorders on Oral Health-Related Quality of Life of Brazilian football athletes: a cross-sectional study (Research, Society and Development, 2022)
Introduction: The athletes who practice sports routinely are exposed to the onset of numerous diseases. Objective: To evaluate oral conditions and their impact on oral health-related quality of life (OHRQoL) in Brazilian football athletes using OHIP-14 questionnaire. Methods: In this cross-sectional study, after sample calculation, football athletes were recruited in Rio de Janeiro, Brazil. Clinical and non-clinical data were collected. Psychometrics properties from OHIP-14 were assessed and the student’s T-test was used to evaluate the associations. Results: From 45 football athletes recruited, after applying the eligibility criteria, 34 athletes were included. The most frequent oral conditions observed were dental erosion (85.3%) and malocclusion (85.3%). OHIP-14 had satisfactory properties (α of Cronbach = 0.80 and test-retest/ICC = 0.90). The mean of impact on OHRQoL was 2.79 (± 3.98). There were association of OHIP-14 total score (p=0.01) and the physical pain subscale (p